2013
DOI: 10.1016/j.wasman.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Removal of carbon constituents from hospital solid waste incinerator fly ash by column flotation

Abstract: Hospital solid waste incinerator (HSWI) fly ash contains a large number of carbon constituents including powder activated carbon and unburned carbon, which are the major source of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in fly ash. Therefore, the removal of carbon constituents could reduce PCDD/Fs in fly ash greatly. In this study, the effects of the main flotation parameters on the removal of carbon constituents were investigated, and the characteristics of the final product were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
(31 reference statements)
1
24
0
Order By: Relevance
“…2(b)] with simultaneous weight loss over a wide temperature range (300°C-600°C); the total weight loss was approximately 61.5%. These results are consistent with the high LOI findings for the froth products (Liu et al, 2013). Because the carbon content of the froths is higher than that of the fly ash, the heat release peak was relatively high.…”
Section: Effect Of Flotation On the Thermal Behavior Of The Fly Ashsupporting
confidence: 89%
See 4 more Smart Citations
“…2(b)] with simultaneous weight loss over a wide temperature range (300°C-600°C); the total weight loss was approximately 61.5%. These results are consistent with the high LOI findings for the froth products (Liu et al, 2013). Because the carbon content of the froths is higher than that of the fly ash, the heat release peak was relatively high.…”
Section: Effect Of Flotation On the Thermal Behavior Of The Fly Ashsupporting
confidence: 89%
“…The hydrophobicity and lipophilicity nature of PCDD/Fs and other organic contaminants such as PAHs, CBs, CPs and PCBs makes them easy to float into the froths after flotation (Cheruiyot et al, 2015;Lee et al, 2016). The previous report indicated that the flotation process could be successfully applied to substantially decrease the amount of carbon constituents and PCDD/Fs in HSWI fly ash (Liu et al, 2013). In that study, the removal efficiency was more than 96% for PCDD/Fs and 92% for carbon constituents.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations